Técnicas de suavização aplicadas à caracterização de fontes sísmicas e à análise probabilística de ameaça sísmica - Pirchiner, Marlon (2014)
Seismic risk assesment is crucial to make better decisions about engineering structures and loss mitigation. It involves, mainly, the evaluation of seismic hazard. Seismic hazard assesment is the computation of probability which the level of some ground motion intensity measure, in a given site, which, in some time window, will be exceeded. Depending on geological and tectonic complexity, the seismic hazard evaluation becomes more sofisticated. At sites with low seismicity, which is the brazilian case, the relative (geolo- gically) low observation time and the lack of earthquake and tectonic information, increases the uncertainties and makes more difficult the standard analysis, which in general, consider expert opinions, to characterize the seismicity into disjoint zones. This text discusses some smoothing seismicity techniques and their theoretical foundati- ons as alternative methods for seismicity characterization. Next, the methods are exemplified in the brazilian context.